IMPACT DYNAMIC BEHAVIOR ANALYSIS OF MULTIPLE LAYERS RE-ENTRANT HONEYCOMB CYLINDRICAL SHELLS (MT) - MA NanFang; DENG QingTian; LI XinBo; SONG XueLi (Jixie qiangdu)
The single layer re-entrant honeycomb cylindrical shell with different angles is established in this paper. Based on the single layer re-entrant honeycomb cylindrical shell with different angles, a novel composite re-entrant honeycomb cylindrical shell is proposed. The deformation behavior of single and multi-layer re-entrant honeycomb cylindrical shells under axial impact was studied by numerical simulation. By comparing and analyzing the plateau stress and specific energy absorption of single and multi-layer re-entrant honeycomb cylindrical shells under different impact velocities. The following conclusions can be obtained: compared with the single-layer re-entrant honeycomb cylindrical shell, the energy absorption capacity of the multi-layer re-entrant honeycomb cylindrical shell is significantly improved under the same density and size. The deformation position of re-entrant honeycomb cylindrical shell is changed with different impact velocities.The multi-layer re-entrant honeycomb cylindrical shell doesn′t show negative Poisson’s ratio.